PRESERVATION OF FISH BY FREEZING AND GLAZING 1. BACTERIOLOGY OF FRESH, FROZEN AND GLAZED FISH - JADHAV, M G; MAGAR, N G (Fishery Technology, 2025)
Microbiological investigation of fresh and frozen fishes such as pomfret, surmai and mackerel was carried out under various conditions of preservation. Glazing, block-freezing and preservation in gunny bag were effected. Determination of bacterial load and isolation, identification and classification of the resistant bacteria were niade. Spore-formers of Subtilis mesentericus group were found to be resistant to freezing as well as glazing by ascorbic acid, citric acid and sodium nitrite except a mixture of sodium chloride and glucose. Bacterial load was reduced to a good extent and maintained low till the end of frozen storage period.